Discursive Agency: (Re‐)Conceptualizing Actors and Practices in the Analysis of Discursive Policymaking. Issue 3 (21st July 2016) - Leipold, Sina; Winkel, Georg
Abstract : Interpretive discourse analysis commonly claims to address the interrelation between actors and discourses. However, the analytical focus of most approaches is on structures (discourses) while much less attention is paid to agency. This paper explicitly addresses discursive agency in two steps. First, we systematically review theoretical and analytical dimensions of agency in existing interpretive discourse analysis approaches. This review reveals a set of shared assumptions; most notably a concept of "trialectic" agency emphasizing the constitution of agency among the individual, the (discursive) structures, and the researcher's interpretation. Second, we propose an analytical heuristic, the Discursive Agency Approach, which is developed on the basis of the review and own empirical data. The proposed approach consists of four elements: (1) policy discourses, (2) political institutions, (3) agents defined via a set of characteristics, and (4) strategic practices. This approach is meant to facilitate a systematic exploration of agency under a discourse perspective, tackling the question of how a policy is constituted through the agency ascribed to its proponents in dynamic discursive processes, and how actors acquire political relevance through discursive means. To enable this goal, we propose distinct research steps and associated methods that link the approach to existing means of analysis. 摘要: 解释性话语分析通常声称分析行为者和话语之间的相互关系。然而, 大多数方法的分析焦点在于结构（话语）, 而较少地关注行为主体。本文通过两方面清楚地分析了话语的行为主体。首先, 我们从理论和分析的层面系统地回顾了现有解释性话语分析方法中的行为主体。这一回顾揭示了一系列共通的前提假设, 尤其是 "三元统一" 的行为主体这一概念。这一概念强调行为主体由个人, （话语）结构, 和研究者的解释组成。其次, 我们根据回顾和自己的实证数据, 作出了一个分析性的探索方案, 即"话语的行为主体分析法"。这一方法包含了四个元素：（ 1 ）政策论述, （ 2 ）政治制度, （ 3 ）具有一系列特征的代理人, 及（ 4 ）策略性行为。这一方法旨在促进从话语角度对行为主体进行系统研究, 通过动态话语过程中的行为主体对于政策的支持来分析一项政策是如何形成的, 以及解释行为者们如何以话语为手段来获取相关的政治信息。为实现该目标, 我们将我们的研究路径与现有的分析方法联系起来, 提出了清晰的研究步骤和相关研究方法。